Exploring the antimicrobial activity of Origanum majorana L. against the highly virulent multidrug-resistant Acinetobacter baumannii AB5075: UPLC-HRMS profiling with in vitro and in silico studies - Norhan H. Mahdally; Abdalla E. M. Salih; Riham A. El-Shiekh; Ahmed M. Sayed; Noha M. Elhosseiny; Mona T. Kashef; Mohammed Yaseen; William Mackay; Ali M. El Halawany; Mostafa E. Rateb; Ahmed S. Attia (SpringerOpen, 2024)
Abstract Background The infamous multidrug-resistant (MDR) bacterium Acinetobacter baumannii is becoming a nightmare in intensive care units across the globe. Since there are now very few effective antimicrobial agents, it is necessary to explore unconventional resources for novel antimicrobials. This study investigated the potential antimicrobial activity of Origanum majorana L. against A. baumannii employing multiple approaches including antimicrobial susceptibility, fractionation, ultra-performance liquid chromatography-high-resolution mass spectrometry (UPLC-HRMS) dereplication, and in silico analysis for target/ligand identification. Results On the extremely pathogenic MDR strain A. baumannii AB5075, O. majorana L. has shown a significant growth inhibitory effect (MIC = 0.675 mg/mL). The polar 50% methanol fraction was the most active (MIC = 0.5 mg/mL). The UPLC-HRMS dereplication of the bioactive fraction detected 29 metabolites belonging to different chemical classes. Justicidin B, one of the identified metabolites, was projected by preliminary in silico analysis to be the most highly scoring metabolite for binding with molecular targets in A. baumannii with a Fit score = 8.56 for enoyl-ACP reductase (FabI) (PDB ID: 6AHE), suggesting it to be its potential target. Additionally, docking, molecular dynamics simulation, and bioinformatics analysis suggested that this interaction is similar to a well-known FabI inhibitor. The amino acids involved in the interaction are conserved among different MDR A. baumannii strains and the effectiveness could extend to Gram-negative pathogens within the ESKAPE group. Conclusions Origanum majorana L. extract exhibits antimicrobial activity against A. baumannii using one or more metabolites in its 50% methanol fraction. The characterized active metabolite is hypothesized to be justicidin B which inhibits the growth of A. baumannii AB5075 via targeting its fatty acid synthesis.